Application of metamaterials for the microwave antenna realizations - Asenov Tatjana; Dončov Nebojša; Milovanović Bratislav (Serbian Journal of Electrical Engineering, 2012)
In this paper, the application of left-handed metamaterials for the realization of microwave antennas has been considered. Special emphasis is placed on lens antennas based on gradient-index metamaterials, and their advantages and enhanced features in comparison with conventional microwave antennas are highlighted.